2019
DOI: 10.31080/asnh.2019.03.0376
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals in Prawn Penaeus merguiensis Collected in 2007 from Sri Serdang Market, Peninsular Malaysia

Abstract: Samples of prawn (Penaeus merguiensis), were collected from a market in Serdang, Selangor, Peninsular Malaysia, in 2007. The prawns samples were dissected into five parts; soft tissue, carapace, periopods, pleopods and telson. The mean metal concentrations (µg/g dry weight) in the soft tissues of the prawns were 89.2 for Fe, 13.6 for Cu, 55.5 for Zn, 0.01 for Cd and 0.01 for Ni. For the human health risk assessment, all values of target hazard quotient for the five metals in the adults of Malaysian population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a study involving the marine shrimp Penaeus merguiensis, Yap et al (2019) reported the concentration of Zn in muscle (55.5 µg/g) and exoskeleton (42.9 µg/g). The higher presence of Zn in shrimp organs is likely linked to the elevated bioavailability of this element in the aquatic environment.…”
Section: Resultsmentioning
confidence: 99%
“…In a study involving the marine shrimp Penaeus merguiensis, Yap et al (2019) reported the concentration of Zn in muscle (55.5 µg/g) and exoskeleton (42.9 µg/g). The higher presence of Zn in shrimp organs is likely linked to the elevated bioavailability of this element in the aquatic environment.…”
Section: Resultsmentioning
confidence: 99%